2014
DOI: 10.1136/jnnp-2014-308097
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and clinical characteristics of orolingual angio-oedema complicating thrombolysis with tissue plasminogen activator for ischaemic stroke

Abstract: Angio-oedema occurs more frequently than previously reported and is associated with preceding ACE-I treatment. Angio-oedema may be delayed and progress to life-threatening airway compromise, which has implications for the assessment and delivery of thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 13 publications
3
49
1
4
Order By: Relevance
“…Prevalence of OA in patients with acute ischemic stroke treated with alteplase was 4.9%, which is in accordance to previous studies [1][2][3][4]7]. We found no significant differences in the frequency of insular cortex ischemic lesions on pre-thrombolysis CT, and early signs of insular cortex ischemia were not independent predictors of OA occurrence in multivariate analysis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Prevalence of OA in patients with acute ischemic stroke treated with alteplase was 4.9%, which is in accordance to previous studies [1][2][3][4]7]. We found no significant differences in the frequency of insular cortex ischemic lesions on pre-thrombolysis CT, and early signs of insular cortex ischemia were not independent predictors of OA occurrence in multivariate analysis.…”
Section: Discussionsupporting
confidence: 80%
“…It consists of painless swelling of lips, tongue, face and occasionally oropharynx, occurring shortly after intravenous alteplase administration, which usually resolves during the first 24 h. Most case-control studies recognize use of angiotensin-converting enzyme inhibitors (ACE-I) as the main risk factor for occurrence of this potentially serious adverse event [1][2][3][4], and other authors found a higher frequency of insular ischemia in patients who developed angioedema [2,5]. In addition to contribute to several high order complex cerebral functions, insular cortex is known to mediate autonomic responses and it is involved in cardiac and vascular autonomic tone regulation and visceromotor control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases resolve spontaneously or with the use of corticosteroids or antihistamines. 19 Other allergic reactions to IV rtPA are rarely reported. 20 Neurological deterioration after IV rtPA is more than twice as likely to be caused by non-haemorrhagic factors (recurrent ischaemic stroke, brain swelling or non-attributable deterioration) than SICH.…”
Section: Complicationsmentioning
confidence: 99%
“…After reading of these 53 articles, 18 were selected for the combined analysis. 11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seventeen articles were published in English 11,[13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29] and 1 in German. 18 The flow chart of the selection of articles is presented in Figure. None of these 18 articles 11,13-29 reported information on the prestroke mRS, alcohol consumption, weight, NIHSS at 2 and 24 hours and at 7 days, presence of infarct on imaging at 22 to 36 hours, s-ICH, infection, malignant infarct, and outcome at 3 months.…”
Section: Review Of the Literaturementioning
confidence: 99%